Effects of Eurycoma longifolia Jack on chronic hypoperfusion-induced oxidative damage and memory deficit in rats - Saleh Alruhaimi, Hulol; Allow, Ahmed Kaid Naji; Buyong, Zunariah; Bahbah, Mohammad Nasser Hamed Mahmoud; Rahman, Shaikh Mizanur (Open Science Publishers LLP, 2019)
Decreased cerebral blood supply, which is associated with dementia, results in chronic cerebral hypoperfusion (CCH), a physiopathological mechanism of neural dysfunction in Alzheimer’s disease. Eurycoma longifolia (EL) Jack has been documented to have multiple biological activities. The current study aimed to determine the potential effect of EL root extracts in CCH using a 2-vessel occlusion (2VO) model. CCH was induced by a permanent bilateral ligation of the common carotid arteries in male Sprague–Dawley rats. The experimental groups were divided as follows: a sham-operated group, a 2VO group without any treatment, and a 2VO group that was orally administered EL extract (100 mg/kg/day) for 3 days before the day of 2VO surgery and continued until the end of postoperative week 8. Spatial memory performance was assessed by the Morris water maze test. Moreover, malondialdehyde (MDA) concentration and superoxide dismutase activity, glutathione level, and C-reactive protein (CRP) concentration in serum were measured. CCH rats showed significant cognitive impairment, decreased antioxidant activities, and increased MDA and CRP concentration in serum. The group that was orally administered EL extract showed a slight preservation of cognitive function, enhanced antioxidant activity, decreased MDA and CRP concentration than did the untreated 2VO group. EL offers potential neuroprotective effects due to its antioxidant and anti-inflammatory properties.